2017
DOI: 10.1038/celldisc.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical biology reveals CARF as a positive regulator of canonical Wnt signaling by promoting TCF/β-catenin transcriptional activity

Abstract: Wnt/β-catenin signaling regulates multiple biological processes and aberration of this pathway is frequently observed in human cancers. Previously, we uncovered NC043 as a small-molecule inhibitor of Wnt/β-catenin signaling. Here, we identified CARF as the cellular target of NC043. We found that NC043 binds directly to CARF through forming a covalent bond with the Cys-516 residue of CARF. Further study revealed that CARF interacts with Dvl, which potentiates the Dvl–c-Jun–β-catenin–TCF transcriptional complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
(45 reference statements)
3
26
0
Order By: Relevance
“…S6b). Furthermore, neither activation of Wnt/β-catenin signaling (endothelium-specific expression of constitutively activated form of β-catenin) 53 nor activation of Ca 2+ signaling (Inomycin treatment) 54,55 could rescue vessel regression phenotype in cds2 mutants with vegfa OE (Supplementary information, Fig. S6c-f).…”
Section: Pip3 Metabolic Exhaustion Governs Vegfa-induced Vessel Regrementioning
confidence: 99%
“…S6b). Furthermore, neither activation of Wnt/β-catenin signaling (endothelium-specific expression of constitutively activated form of β-catenin) 53 nor activation of Ca 2+ signaling (Inomycin treatment) 54,55 could rescue vessel regression phenotype in cds2 mutants with vegfa OE (Supplementary information, Fig. S6c-f).…”
Section: Pip3 Metabolic Exhaustion Governs Vegfa-induced Vessel Regrementioning
confidence: 99%
“…This molecule also inhibited tumour growth in a SW480 colon cancer xenograft mouse model in a dose‐dependent manner by up to ~70%. A detailed follow‐up study with the goal of determining the inhibitory mechanism of NC043 found that this molecule covalently binds to CARF (collaborator of ARF), a protein with context‐dependent effects on proliferation (He et al, ). Through a series of biochemical and proteomic studies, CARF was found to interact directly with DVL in the nucleus and to potentiate the formation of the TCF/LEF–β‐catenin complex and transcription of Wnt target genes (He et al, ).…”
Section: Compounds Targeting Wnt Co‐factorsmentioning
confidence: 99%
“…A detailed follow‐up study with the goal of determining the inhibitory mechanism of NC043 found that this molecule covalently binds to CARF (collaborator of ARF), a protein with context‐dependent effects on proliferation (He et al, ). Through a series of biochemical and proteomic studies, CARF was found to interact directly with DVL in the nucleus and to potentiate the formation of the TCF/LEF–β‐catenin complex and transcription of Wnt target genes (He et al, ). The authors concluded that NC043 could covalently bind to CARF and disrupt its interaction with DVL, which then led to inhibition of β‐catenin‐dependent Wnt signalling in the nucleus.…”
Section: Compounds Targeting Wnt Co‐factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG-001 has been found to compete with CREB-binding protein for binding ␤-catenin, thereby inhibiting Wnt signaling (7). Our laboratory recently reported NC043 as a Wnt signaling inhibitor by targeting CARF (collaborator of ARF) to disturb TCF4 and ␤-catenin interaction (8,9). PTL, a sesquiterpene lactone, was first purified from the shoots of the medicinal plant feverfew (Tanacetum parthenium) (10,11), which is a Chinese folk medical plant and has been used to treat fever, headache, and arthritis for many years (12).…”
mentioning
confidence: 99%